Framing an argument of Normalization with Israel on the websites of directed satellite channels Analytical study of the sites (Al-Alam, Al-Hurra) channels - kamil jawad, Aymen (ALBAHITH ALALAMI, 2021)
The aim of this paper is to study the frames of Argument of normalization with Israel on the websites of the satellite channels directed in the Arabic language (Al-Alam and Al-Hurra Iraq) channels by analyzing the mechanisms of framing an Argument, The way in which we frame an issue largely determines how that issue will be understood and acted upon، The research adopted the survey method applied to the sites of(Al-Alam and Al-Hurra) channels, at the period 13 Aug. - 12 Nov. 2020, which included (855) news items, (633) for Al-Alam channel website, and (222) for Alhurra Iraq channel website.The most important results are: The two channels dependence on the Argument Directed, Al-Alam channel focuses on Islamic and Arab attitudes, At the level of religious and governmental leaders or the audience, While Al-Hurra Iraq channel proposed it by convincing the recipient to the political and economic benefits. The results also confirmed the interest of the two channels' sites in the fixed images that topped the list of elements accompanying the arguments, in addition to, Al-Alam channel Brought out the ethical frame in the Argument of normalization in the first rank in support their arguments. based on the fact that normalization is a betrayal of religion and Arabism, while Al-Hurra focused on the frame of cooperation in the first rank.